Comparative of cultural material study between Baba Nyonya original descendants and Baba Nyonya new descendants in Malacca - Farhana Abd Kadir (Tanjong Malim, 2022)
Comparative of cultural material study between Baba Nyonya original descendants and Baba Nyonya new descendants in Malacca by Farhana Abd Kadir